2021
DOI: 10.3390/molecules26226913
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation Pattern of Flavonoids during Fruit Development of Lonicera maackii Determined by Metabolomics

Abstract: Lonicera maackii (Caprifoliaceae) is a large, upright shrub with fruits that contain many bioactive compounds. Flavonoids are common active substances in L. maackii. However, there is a dearth of information about the accumulation of these flavonoids and their possible medicinal value. We used targeted metabolomics analysis based on ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) to analyze five developmental stages of L. maackii fruit. A total of 438 metabolites were identified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Flavonoid contents may be strongly affected by genetic heritage and epigenetic modification as mechanisms of plant responses to environmental stress [ 35 ]. Qi et al, 2020 reported dynamic changes and significant differences in the accumulation of flavonoids during the development stages of Lonicera maackii fruit [ 38 ]. Quercetin and rutin as the most common flavonoids show therapeutic effects; the former influences lipid accumulation and eliminates inflammation in non-alcoholic fatty liver, the other can attenuate neuroinflammation, improve memory deficits and delay pathological processes of Alzheimer’s disease [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoid contents may be strongly affected by genetic heritage and epigenetic modification as mechanisms of plant responses to environmental stress [ 35 ]. Qi et al, 2020 reported dynamic changes and significant differences in the accumulation of flavonoids during the development stages of Lonicera maackii fruit [ 38 ]. Quercetin and rutin as the most common flavonoids show therapeutic effects; the former influences lipid accumulation and eliminates inflammation in non-alcoholic fatty liver, the other can attenuate neuroinflammation, improve memory deficits and delay pathological processes of Alzheimer’s disease [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Qi et al, 2020 reported dynamic changes and significant differences in the accumulation of flavonoids during the development stages of Lonicera maackii fruit [ 38 ]. Quercetin and rutin as the most common flavonoids show therapeutic effects; the former influences lipid accumulation and eliminates inflammation in non-alcoholic fatty liver, the other can attenuate neuroinflammation, improve memory deficits and delay pathological processes of Alzheimer’s disease [ 38 ]. Catechins also provide several health benefits by scavenging free radicals and directly affect the properties of the skin by activating synthesis of collagen [ 39 ].…”
Section: Resultsmentioning
confidence: 99%